2004
DOI: 10.1016/j.peptides.2004.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Study in vitro and in vivo of nociceptin/orphanin FQ(1–13)NH2 analogues substituting N-Me-Gly for Gly2 or Gly3

Abstract: In the present study, two analogues containing N-Me-Gly (Sarcosine, Sar) were synthesized to further investigate the structural-activity relationships of orphanin FQ/nociceptin (OFQ/NC, NC). The replacement of Gly 2 or Gly 3 with Sar increased the flexibility and decreased the hydrophobicity of the N-terminal tetrapeptide. The activity of the analogues was investigated in a series of assays in vivo and in vitro.[Sar 2 ]NC(1-13)NH 2 was found to (1) produce dose-dependent inhibition of the electrically induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…As previous preclinical and clinical studies have reported sex-specific differences in COMT-related phenotypes 79-83 and as males and females exhibit different COMT expression patterns, 84,85 we examined the contribution of peripheral adrenergic systems to COMT-dependent pain in both males and females. Counter to our expectation, male and female rats exhibited a comparable increase in mechanical and thermal pain following sustained systemic OR486 administration, which was blocked by suppressing peripheral adrenergic tone.…”
Section: Discussionmentioning
confidence: 99%
“…As previous preclinical and clinical studies have reported sex-specific differences in COMT-related phenotypes 79-83 and as males and females exhibit different COMT expression patterns, 84,85 we examined the contribution of peripheral adrenergic systems to COMT-dependent pain in both males and females. Counter to our expectation, male and female rats exhibited a comparable increase in mechanical and thermal pain following sustained systemic OR486 administration, which was blocked by suppressing peripheral adrenergic tone.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-established that males and females differ with respect to COMT activity levels, with males exhibiting higher levels in brain (Chen et al, 2004) and peripheral tissues (Boudikova et al, 1990). A growing literature continues to demonstrate that the effects of COMT on nociception, cognition, and behavioral traits such as anxiety are sexually dimorphic, with the magnitude and direction of the effect being highly assay-dependent (Gogos et al, 1998, Harrison and Tunbridge, 2008, Papaleo et al, 2012, Belfer et al, 2013, Sannino et al, 2014, White et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…As previous preclinical and clinical studies have reported sex differences in COMT-related phenotypes 5, 29, 36, 75, 105 and COMT expression patterns 7, 10 , we examined the effects of acupuncture in both males and females. We found that male and female mice in this study exhibited comparable increases in mechanical pain following sustained delivery of OR486.…”
Section: Discussionmentioning
confidence: 99%